Assessment of Healthy Colonic Motility Patterns, Colonic Dysmotility, and its Association with Autonomic Nervous System Dysfunction - Milkova, Natalija (My University, 2020)
Introduction: Functional motility disorders of the colon are poorly defined. Hence, patients with chronic colonic motor dysfunction are treated or undergo surgery without proper diagnosis. Most colonic motility assessment centers around the largest propagating motor pattern in the colon- the High Amplitude Propagating Pressure Wave (HAPW). However, there is no consensus regarding a definition of this important motor pattern. Additionally, no consideration is given to other aspects of colonic motility such as colo-ano-rectal coordination and control by the autonomic nervous system (ANS). The aim of this thesis was to improve understanding of HAPWs and other features of colonic motility in health and constipation, understand how autonomic dysfunction is related to observations in patients, and evaluate the effect of neuromodulation of the ANS. Methods: Motility was assessed in healthy volunteers and patients using water-perfused High Resolution Colonic Manometry (HRCM). To assess the association between ANS and colonic motor activity Heart Rate Variability (HRV) was measured in patients. Spatiotemporal maps were created using HRCM to analyse and quantify colonic motor activity following baseline, and interventions which included proximal balloon distention, meal, and rectal bisacodyl. Low-Level Light Therapy (LLLT) was also applied during HRCM as a method of neuromodulation, to observe its effect on colonic motility. Results: Normal HAPWs are those which have an amplitude of more than 50 mmHg and belong to one of 3 categories: proximally originating, proximal continuing, and transverse/descending. The best intervention sequence to generate these during HRCM assessment is baseline, proximal balloon distention, meal, rectal bisacodyl. Based on their responses to these interventions and the type of HAPWs present, patients could be classified into strong responder, weak responder and non-responder groups. Overall, patients in the strong responder group were most similar to healthy volunteers both with regard to motility and ANS control. Conversely, the weak and non-responders had showed decreased or no motility with decreased parasympathetic input and occasionally sympathetic inhibition. Additionally, other features of motility such as the sphincter of O'Beirne, and lack of colo-ano-rectal coordination were found to lead to constipation even in presence of normal HAPWs. LLLT shows promise in initiating colonic motor activity through neuromodulation of the sacral defecation center. Conclusions: HAPWs can be defined into one of three categories and used to categorize patients based on their HAPW response to different interventions. However, other aspects of colonic motility such as the colo-ano-rectal coordination and autonomic nervous system control of colonic motility should be taken into consideration in diagnosis of constipation, as they can point towards more non-invasive treatment methods such as neuromodulation using LLLT.
Keywords: colonic motility; high resolution colonic manometry; high amplitude propagating pressure waves; human colon; functional motility disorders; gastroenterology